### Home > PC > Chapter 4 > Lesson 4.1.4 > Problem 4-59

4-59.

Michelle has the problem (2*x* + 3)^{2} − 3(2*x* + 3) − 10 = 0 and is thinking of expanding the (2*x* + 3) terms and then solving. Erin suggests that she let *a* = 2*x* + 3 then solve *a*^{2} − 3*a* − 10 = 0. Use Erin’s suggestion to solve for *a* and then use your solutions to find the values of *x*. Homework Help ✎

Solve for the values of *a* first.

Then substitute the values of *a* into *a* = 2*x* + 3.

Finally, solve for *x*. You should get two answers.